Occurrence and transformation of veterinary antibiotics and antibiotic resistance genes in dairy manure treated by advanced anaerobic digestion and conventional treatment methods. (May 2018) - Wallace, Joshua S.; Garner, Emily; Pruden, Amy; Aga, Diana S.
Abstract: Manure treatment technologies are rapidly developing to minimize eutrophication of surrounding environments and potentially decrease the introduction of antibiotics and antibiotic resistant genes (ARGs) into the environment. While laboratory and pilot-scale manure treatment systems boast promising results, antibiotic and ARG removals in full-scale systems receiving continuous manure input have not been evaluated. The effect of treatment on ARGs is similarly lacking. This study examines the occurrence and transformation of sulfonamides, tetracyclines, tetracycline degradation products, and related ARGs throughout a full-scale advanced anaerobic digester (AAD) receiving continuous manure and antibiotic input. Manure samples were collected throughout the AAD system to evaluate baseline antibiotic and ARG input (raw manure), the effect of hygenization (post-pasteurized manure) and anaerobic digestion (post-digestion manure) on antibiotic and ARG levels. Antibiotics were analyzed by liquid chromatography-tandem mass spectrometry (LC-MS/MS), and the ARGs tet (O), tet (W), sul 1 and sul 2 were analyzed by quantitative polymerase chain reaction (Q-PCR). Significant reductions in the concentrations of chlortetracycline, oxytetracycline, tetracycline and their degradation products were observed in manure liquids following treatment (p < 0.001), concomitant to significant increases in manure solids (p < 0.001). These results suggest sorption is the major removal route for tetracyclines during AAD. Significant decreases in the epimer-to-total residue ratios for chlortetracycline and tetracycline in manure solids further indicate degradation is desorption-limited. Moreover, sul 1 and sul 2 copies decreased significantly (p < 0.001) following AAD in the absence of sulfonamide antibiotics, while tetracyclines-resistant genes remained unchanged. A cross-sectional study of dairy farms utilizing natural aeration and liquid-solid separation treatments was additionally performed to compare levels of antibiotics and ARGs found in AAD with the levels in common manure management systems. The concentration of antibiotics in raw manure varied greatly between farms while minimal differences in ARGs were observed. However, significant (p < 0.01) differences in the levels of antibiotics and ARGs (except tet (W)) were observed in the effluents from the three different manure management systems. Graphical abstract: Image 1 Highlights: Tetracyclines (TETs) were detected in manure pre and post advanced digestion (AAD). TETs increased in manure solids and decreased in liquids after AAD. TET-epimer ratios suggest degradation rates and mechanisms differ in AAD. sul 1 and sul 2 genes decreased by approx. 5% and 10%, each after AAD. Seasonal variation in TET inputs not correlated with ARG changes in effluent. Abstract : Anaerobic digestion of dairy manure utilizing pre-digestion pasteurization significantly reduced tetracycline concentrations in effluent liquid manure and increased in effluent solids while demonstrating a significant (p < 0.01) decrease in the copies of sulfonamide antibiotic resistance genes sul 1 and sul 2 in the absence of detectable sulfonamide antibiotics.